Cardiovascular Risk Profiles amongst Women in a Multiethnic Population in Inner City Britain: A Potential Impact of Anaemia - Julia Chackathayil; Jeetesh V. Patel; Paramjit S. Gill; Rahul Potluri; Ammar Natalwala; Hardeep Uppal; Deepthi Lavu; Reinhard Heun; Elizabeth A. Hughes; Gregory Y. H. Lip (International Journal of Endocrinology)
The risk of diabetes is markedly reduced in men with iron deficiency anaemia (IDA). The nature of this relationship in women is not clear, nor is there information about the influence of ethnicity, given the increased susceptibility of diabetes amongst South Asians and Afro-Caribbeans. We reviewed 3563 patients with a diagnosis of anaemia from 2000 to 2007. The age-adjusted prevalence of vitamin B12 deficiency and IDA was calculated, together with cardiovascular comorbidities amongst Caucasians, South Asians, and Afro-Caribbeans. The prevalence of vitamin B12 deficiency (women only) or IDA was markedly higher in South Asians compared to Caucasians and Afro-Caribbeans. Among women with IDA, diabetes was more prevalent among South Asians (45%, 95% CI 39.0–51.0) compared to Caucasians (3.0%, 2.1–4.0); P<0.001. Among South Asian women with vitamin B12 deficiency, the prevalence of diabetes was reduced 8.5% (5.2–12.0). South Asian women with vitamin B12 deficiency had a higher prevalence of myocardial infarction (MI) and ischemic heart disease (IHD), but this relationship was reversed in IDA. IDA is associated with a greater prevalence of diabetes in South Asian women, but it is not coordinated by a greater risk of macrovascular complications. Given the cardiovascular impact of diabetes in South Asians, this association merits further study in relation to its pathophysiological implication.